Characteristics and Management of IgA Vasculitis (Henoch‐Schönlein) in Adults: Data From 260 Patients Included in a French Multicenter Retrospective Survey. Issue 9 (29th August 2017) - Audemard‐Verger, Alexandra; Terrier, Benjamin; Dechartres, Agnès; Chanal, Johan; Amoura, Zahir; Le Gouellec, Noémie; Cacoub, Patrice; Jourde‐Chiche, Noémie; Urbanski, Geoffrey; Augusto, Jean‐François; Moulis, Guillaume; Raffray, Loic; et al.
Abstract : Objective: Data on adult IgA vasculitis (Henoch‐Schönlein) (IgAV) are scarce. This survey was designed to better define the clinical spectrum of IgAV and efficacy of treatments in a French patient population. Methods: Data on clinical characteristics, histologic features, and treatment response from 260 patients with IgAV included in a French multicenter retrospective survey were analyzed. Efficacy data were compared using different statistical models. Results: The mean ± SD age of the patients with IgAV at diagnosis was 50.1 ± 18 years, and 63% of patients were male. Baseline manifestations included purpura (100%), arthralgias/arthritis/myalgia (61%), glomerulonephritis (70%), and/or gastrointestinal involvement (53%). Thirty percent of patients showed renal failure at baseline. In univariate analysis, the response to therapy was 80% (64 of 80) in patients treated with corticosteroids (CS) alone, compared to 77% (23 of 30) in patients treated with CS plus cyclophosphamide (CYC) and 59% (10 of 17) in patients treated with colchicine ( P  = 0.17). Multivariable analysis showed that treatment with CS or CS plus CYC was more effective than colchicine in achieving a response. Efficacy differences were demonstrated using different statistical models: in the multivariable logistic regression model, odds ratio (OR) 3.68, 95% confidence interval (95% CI) 1.10–12.33 ( P  = 0.03); in the inverse probability weighting on propensity score model, OR 3.75, 95% CI 1.28–10.99 ( P  = 0.02). The efficacy of CS plus CYC as compared to CS alone was discordant according to the analytic method used. Analysis with the multivariable logistic regression model did not demonstrate a difference between CS plus CYC and CS alone (OR 0.88, 95% CI 0.29–2.67; P  = 0.82). In contrast, inverse probability weighting on propensity score showed that CS plus CYC was more effective than CS alone (OR 1.79, 95% CI 1.00–3.20; P  = 0.049). Conclusion: This series constitutes the largest series of adults with IgAV reported in the literature so far. It provides data on clinical and histologic presentation and therapeutic efficacy, suggesting that CS alone appears to be a reasonable first‐line therapy in patients with IgAV, while the benefit of adding CYC to CS remains uncertain.